2019
DOI: 10.1021/acssuschemeng.8b05658
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroabietylamine-Based Cellulose Nanofibril Films: A New Class of Sustainable Biomaterials for Highly Efficient, Broad-Spectrum Antimicrobial Effects

Abstract: The design of antimicrobial surfaces as integral parts of advanced biomaterials is nowadays a high research priority, as the accumulation of microorganisms on surfaces inflicts substantial costs on the health and industry sectors. At present, there is a growing interest in designing functional materials from polymers abundant in nature, such as cellulose, that combine sustainability with outstanding mechanical properties and economic production. There is also the need to find suitable replacements for antimicr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
(63 reference statements)
2
8
0
Order By: Relevance
“…Cascaroside B, putatively identified in the present study, is a well-known flavonoid and was previously reported to possess antifungal properties [56]. The antifungal activities of dehydroabietylamine, epiandrosterone, and nocodazolewere previously reported [57][58][59]. Pyochelin, reported in the present study, was previously known as an iron chelator produced in endophytes.…”
Section: Plos Onesupporting
confidence: 57%
“…Cascaroside B, putatively identified in the present study, is a well-known flavonoid and was previously reported to possess antifungal properties [56]. The antifungal activities of dehydroabietylamine, epiandrosterone, and nocodazolewere previously reported [57][58][59]. Pyochelin, reported in the present study, was previously known as an iron chelator produced in endophytes.…”
Section: Plos Onesupporting
confidence: 57%
“…26 Despite these general considerations, there is yet another feature of CNF films functionalized with dehydroabietic acid derivatives that is highly relevant when discussing their potential mode of action. In line with our previous observations, 58 charge, hydrophobicity, and surface topography Statistical analysis was done using a 2-tailed independent t-test. CNF-CMC-7b showed an average reduction in recovered CFU of 1.4 log (95% CI: 0.9−1.9, p < 0.05, n = 9) compared to CNF.…”
Section: ■ Results and Discussionmentioning
confidence: 91%
“…Never-dried birch kraft pulp was used to prepare CNF films, as reported previously. 58 The pulp dispersion was obtained by disintegrating using a high-pressure fluidizer (Microfluidics, M-110Y, Microfluidics Int. Co., Newton, MA) and ACS Applied Bio Materials circulated for 6 passes.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Polymer brushes are highly efficient in preventing organic and biological fouling , but require a laborious synthesis and harmful chemicals. The production of carbon-based nanomaterials also requires complicated and time-consuming processes. , Metallic nanoparticles can be easily synthesized, and their microbial toxicity has been studied at length . Still, their toxicity to aquatic organisms, persistence in the environment, and ability to trigger resistance mechanisms in bacteria limit their application .…”
Section: Introductionmentioning
confidence: 99%